Facial fractures due to bicycle accidents in pediatric and adolescent patients - Muñante-Cárdenas, José (2010)
The objective was to perform a retrospective analysis of the incidence, characteristics, use of safety devices, treatment and complications of the maxillofacial trauma caused by bicycle accidents. The sample was selected from analysis of 2986 medical records from patients treated between 1999 and 2008 by the Department of Oral and Maxillofacial Surgery of the Faculty of Dentistry of Piracicaba, State University of Campinas (FOP-UNICAMP), State of São Paulo, Brazil. During this period, 757 patients under 18 years were treated, of which 220 were victims of bicycle accidents. The bicycle accidents constituted 29 % of the facial trauma. Only 1,8 % of the patients made use of safety devices. The adolescents were the most affected and the male gender was the most prevalent. 69 facial fractures were identified, being the jaw the most affected (55,1 %). The conservative treatment was used in most of the cases (72,4 %), while only one case of postoperative complication was reported. It is concluded that bicycle accidents represented the main etiology of the maxillofacial trauma, being the male gender predominant in all age groups evaluated. The mandibular fractures were the most prevalent and the majority of patients did not use any type of safety device.